Perception Analysis of Purchasing Attitude And Willingness To Pay For Coffee and Non-Coffee Beverage Products - Yurika Rahayu, Yurika Rahayu; Sumarwan, Ujang; Asnawi, Yudha Heryawan (Jurnal Manajemen & Agribisnis, 2023)
The development of the current era has changed people's lifestyles in enjoying beverage products, especially coffee. This research aims to analyze consumer characteristics, the influence of perceptions on purchasing attitudes, and WTP or Willingness To Pay consumer for coffee and non-coffee beverage products. This research uses purposive sampling with a questionnaire as a sampling technique. The sample obtained was 213 respondents. The collected data was analyzed with the SPSS26 program using logistic regression and conjoint methods. The regression results show that when there is an increase in the price of coffee beverage, the taste and price show that quality variables has an influence on consumer purchasing attitudes, so consumers will reduce purchases, and there is a decrease in the price of coffee beverage, taste and discount promotion variables influence consumer purchasing attitudes, so consumers will increase purchase. Meanwhile, there is an increase prices for non-coffee beverage products, taste, menu variant and aroma variables influence consumer purchasing attitudes, so consumers will reduce purchases. and when there is a decrease in the price of non-coffee beverages, the taste and buy1free1 promotions variables influence purchasing attitudes, so consumers will increase purchases. For the result of the konjoin analysis, the combination of attributes that consumers like most is menu variations and buy 1 get 1 free promotion. Keywords: consumer perception, conjoint analysis, logistik regression, purchasing attitude, willingness to pay